P74 A Novel Measure of Physical Exercise Capacity in COPD. (19th November 2012) - Albarrati, AM; Gale, NG; Duckers, J; Enright, S; Munnery, I; Munnery, M; Cockcroft, JR; Shale, DJ
Abstract : Introduction: Chronic obstructive pulmonary disease (COPD) is associated with progressive impairment of physical performance. However, determination of physical performance in routine clinical practise is difficult due to limited resources. This study compared the timed up and go (TUG) test and a range of assessments of physical performance, easily applied in the routine care of COPD, with the 6 minute walk test (6MWT). Method: As part of a longitudinal study of comorbidities in COPD, sub-maximal physical performance was examined in 300 patients and 50 comparators using the 6MWT. The TUG test, spirometry, COPD assessment test (CAT), St George's Respiratory Questionnaire (SGRQ) and gait speed were also determined. Gait speed was determined by dividing 6MWTd istance by time. Results: Patients and comparators were similar in age, BMI and gender. There were between group differences in 6MWT, TUG and gait speed (Table 1 ), ANOVA showed a difference between comparators and the GOLD stages of COPD for all these variables (all p<0.01). The TUG time differed across BMI categories in COPD but not comparators (ANOVA p=0.007 and p=0.195 respectively). The TUG time was inversely related to 6MWT (r=0.64, p<0.0001), gait speed (r=0.63, p<0.0001)and lung function (r=0.15, p<0.01), and directly to the activity (r=0.35, p<0.0001)and total SGRQ scores (r=0.35, p<0.0001) and CAT (r=0.39, p<0.0001). Stepwise regression analysis, adjusted for age and BMI, indicated that TUG time, SGRQ activity score and CAT score explained 73% of variance in 6MWT in patients, with lung function excluded from the analysis. Conclusions: The TUG time identified the difference in physical performance between patients and comparators and also across GOLD categories. In the elderly the TUG test has been used as an indicator of physical performance, being an integrated measure of gait speed, balance and functional capacity. It appears to apply in the same way to the physical deficits in COPD and also to link to health related quality of life. The application of TUG test and validated questionnaires may be a useful measure of physical performance, which because of its rapidity and ease of application could be used in assessments in clinical practise.